البدئل الحديثة للدعوى الجنائية التقليدية دراسة مقارنة - Salem Alem Ramadan Abo Baker (Universiti Sains Islam Malaysia, 2024)
The new alternatives for criminal prosecution takes an important position in the comparative legislations to face the pressure on courts, also these alternatives consider the principle of reconciling between fast justice and the shortness in formal procedures. Therefore, this study aims to solve the problem of imbalance between the effectiveness of criminal procedures and preserve individual guarantees between the parties involved in the criminal prosecution. In particular the victim because they are the forgotten party and the establishment of criminal justice under the legislation and Libyan criminal law, which is the aim of this study by identifying the alternatives for Criminal prosecution as a new procedural system aims to show the level of effectiveness of this systems in achieving criminal justice and contributing to overcome the crises of criminal justice as well as highlighting the importance of community participation because it is parallel with new criminal policy in an attempt to develop a model that can be implemented in the countries of the Arab World that is compatible with its Islamic trends and Sharia. The researcher used the analytical method and comparative approach to trace the origins of this system and the analysis of legal and the legitimate texts and then conduct a comparison between them. The researcher found that the shift from the criminal procedure and finding modern alternatives in managing criminal justice is very important and one of the necessities of criminal policy due to the strength of its bases and justifications, and how the will opponents takes an important role in deciding the criminal prosecution, and this is according to the consensual principle which many alternatives of criminal prosecutions are based on such as conciliation. In this study the extent of the authority that gave the legislator entrusted to investigate the termination of criminal proceedings based on the compatibility as a principle for other alternatives, which are represented in criminal issues. The researcher recommends that the application of those alternatives with the support of the judiciary to raise them to a level of judicial rulings, also it is important to abandon even partially the regulations that are not effective anymore to face an important part of crimes, which is based on militancy both in terms of the expansion of criminalization and severer penalties, and to replace them by simple procedural methods that contribute to finalize the prosecution and managing it in a simple way that reduces the pressure on the management of criminal justice.